2015
DOI: 10.3168/jds.2014-9296
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of visceral pain associated with metritis in dairy cows

Abstract: Metritis is a common disease in dairy cattle, but to our knowledge, no work has assessed pain associated with this disease. Tissue palpation is commonly used to assess pain in human and veterinary medicine. The objective of this study was to evaluate visceral pain responses during rectal palpation, with and without uterine palpation, in healthy cows and in cows diagnosed with metritis. A total of 49 Holstein dairy cows (mean ± standard deviation parity of 2.8±1.8) were subjected to systematic health checks eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 46 publications
2
55
0
8
Order By: Relevance
“…Chenault et al (2004) and McLaughlin et al (2012) found greater clinical cure (15-19 percentage points) for cows treated with ceftiofur compared with untreated control cows. Because of several concerns such as animal welfare, painful disease, and economic losses (Drillich et al, 2001;Lima et al, 2014;Stojkov et al, 2015), we did not include an untreated control group in our experiment. Therefore, we cannot determine whether the cows initially treated with ketoprofen that did not need extT self-cured or recovered due to the antiinflammatory, antipyretic, and analgesic effects of the NSAID.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Chenault et al (2004) and McLaughlin et al (2012) found greater clinical cure (15-19 percentage points) for cows treated with ceftiofur compared with untreated control cows. Because of several concerns such as animal welfare, painful disease, and economic losses (Drillich et al, 2001;Lima et al, 2014;Stojkov et al, 2015), we did not include an untreated control group in our experiment. Therefore, we cannot determine whether the cows initially treated with ketoprofen that did not need extT self-cured or recovered due to the antiinflammatory, antipyretic, and analgesic effects of the NSAID.…”
Section: Figurementioning
confidence: 99%
“…Cows with APM have signs of systemic illness, are at greater risk of an impaired reproductive performance, are more likely to be culled, and have a greater risk of reduced milk production in comparison to healthy cows (Fourichon et al, 2000;Sheldon et al, 2006;Wittrock et al, 2011). Moreover, APM is a painful disease, and the pain response is particularly obvious during transrectal palpation of the uterus (Stojkov et al, 2015). In consequence, animal welfare as well as economic reasons illustrate the need of an effective treatment.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that a negative energy balance caused by reduction in feed intake led to immunosuppression and thus infection (Ingvartsen and Andersen, 2000;Sordillo and Raphael, 2013). The protracted reduction in eating time may have been linked to pain caused by uterine inflammation (Stojkov et al, 2015). It was shown that cows with retained placenta alone and cows with retained placenta followed by metritis had a reduction in feed intake by 18 and 22 to 55%, respectively (Zamet et al, 1979b;Laven and Peters, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…The disease compromises animal welfare as it causes visceral pain (Stojkov et al 2015) and has an economical impact due to detrimental effects on reproductive performance, milk production and survivability (Overton and Fetrow 2008).…”
mentioning
confidence: 99%